Possibility or Barrier? The Influence of Digitalization on the Adaptation of Student-Migrants (The Case of Siberia) - Koreshkova, Iuliia; Ivanov , Kirill (Italian Sociological Review, 2024)
In this study, we report on how the consumption of digital technologies has impacted the process of settling-in of two groups of student-migrants to the Irkutsk region in Siberia: trans-local Russians and transnational Chinese. The article demonstrates that the consumption of digital technologies and participation in diverse digital communities modulate the spatial practices of educational migrants and, consequently, the perception of space itself, which plays a crucial role in the adaptation process. Participation in social media groups by the Chinese is vital. Social media mark up the urban space (city, dormitory, institute, shopping places, leisure places, etc.) into (not)necessary for consumption, which “completes” a set of perceived places. For Russians, social media serves only as an addition to offline practices. They play a “servicing” role, often allowing them not to contact once again offline. At the same time, the potential opportunities for Russian students to build networks and visit new places in everyday life remain wider and do not have “Chinese” restrictions - places or chat rooms. Additionally, the investigation proves that being physically every day at the same time and in the same places, local and international students perceive them differently, and a large part of this difference derives from the digital resources they communicate and obtain information. As a result, despite the mutual interest and physical presence of both Chinese students and learners of Chinese, contact between these groups throughout the educational track remains low.